Fostering Student-Faculty Engagement and Increasing Learning in the Ongoing Quest for Online Quality - Donavant, Brian W (Advances in Social Sciences Research Journal, 2023)
As online delivery of higher education programs continues to increase, a scarcity of empirical research assessing the efficacy of online pedagogy exists. Believing that a focus on learning is more important than the touted accolades of access and convenience, this experimental study examined how best to leverage specific components of technology to provide engaging and meaningful faculty-student interaction that actually increases learning within online courses. The results indicate that the use of digital presentations narrated and provided by the instructor of record rather than course material incorporated from static presentations or other external sources brought about a statistically significant increase in learning improvement compared to the use of more traditional online tools. Amid the clamor for academic quality and accountability within higher education programs, the results and context of this study provide direction for future discussions and research as well as immediate implications for online education praxis.